Relationships between Service Quality, Brand Image, Customer Satisfaction, and Customer Loyalty of UC Makassar - Wijaya, Justin; Putra, Sinar Dharmayana (Jurnal Entrepreneur dan Entrepreneurship, 2023)
Economic development in recent years has been driven among others by the service industry. The fierce competitive situation has driven competing businesses to continually develop themselves to provide superior quality services and an excellent brand image to gain customer satisfaction and loyalty. This study aims to examine the relationships between service quality, brand image, customer satisfaction, and customer loyalty of UC Makassar. We collect research data from 68 students using a convenient sampling technique. We adopted the conceptual model from prior studies. PLS-SEM was conducted to test the relationships in the conceptual models. The outcomes indicate that customer satisfaction has a positive impact on customer loyalty. The findings also found that service quality positively affects brand image and customer satisfaction but not loyalty. Likewise, brand image has a positive effect on customer satisfaction but not on loyalty. The implications of this research, limitations, and directions for further research can be found below.